Do Overlapping Land Rights Reduce Agricultural Investment? Evidence from Uganda - Deininger, Klaus; Ali, Daniel Ayalew (2012)
While the need for land-related investment for sustainable land management and increased productivity is well recognized, quantitative evidence on agricultural productivity effects of secure property rights in Africa is scant. Within-household analysis of investments by owner-cum-occupants in Uganda points toward significant and quantitatively large investment effects of full ownership. Registration is estimated to have no investment effects, whereas measures to strengthen occupancy rights attenuate investment disincentives. While this supports the importance of secure tenure as a precondition for growth, it also suggests that interventions aiming to increase tenure security need to be context-specific for it to be fully effective.